Caos y consciencia. Una introducción al pensamiento de Walter J. Freeman - Cela Conde, Camilo J.; Marty, GisèLe (Psicothema, 1995)
This paper tries to introduce Freeman’s theory on chaotic processes in the brain as the background to knowledge construction. Experimental study in the field of olfactory perception shows that internally generated neural processes prepare the organism to seek out inputs coming from the external world. The system dynamics are nonlinear: organized state appears when inhaling, and exhalation drives to chaotic states. The world image is made by spatial patterns of neuronal network activity which emerge from the chaos. Some epistemological consequences of that model have special psychological significance: a. In an associative memory system, each new memory alters the old ones when becoming tied to them. This process takes place at the macroscopic level (neural networks) and not at the microscopic one (isolated neurons). There is no place into Freeman’s model neither for "grandmother neurons", nor for invariant memory stores. b. The lack of pattern invariance contrasts with behavioral stimulus-response invariance. The same Freeman gives an answer to this paradox in the interview included in this issue of Psicothema. c. The sole "information" successfully transmitted from olfactory bulb to deeper areas of the brain is an active perceptual construct. d. If we can extend the former idea to other sensory systems in different species -as human species-, then we must conclude that there is no "information processing mechanism" in the brain (as supposed by cognitive functionalists) but just perceptual constructs based on individual experiences. Information is constructed, not processed, through deterministic chaotic dynamics. e. Both subject purposes and environment impose the circumstances for neural activity. Therefore, intentionality becomes the main key for knowledge construction.